2023
DOI: 10.1083/jcb.202306120
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Atg15-mediated membrane disruption in autophagy

Yoko Kagohashi,
Michiko Sasaki,
Alexander I. May
et al.

Abstract: Autophagy is a lysosomal/vacuolar delivery system that degrades cytoplasmic material. During autophagy, autophagosomes deliver cellular components to the vacuole, resulting in the release of a cargo-containing autophagic body (AB) into the vacuole. AB membranes must be disrupted for degradation of cargo to occur. The lipase Atg15 and vacuolar proteases Pep4 and Prb1 are known to be necessary for this disruption and cargo degradation, but the mechanistic underpinnings remain unclear. In this study, we establish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The amino acid sequence of the Atg15 (QHB07198.1_SC) yeast with 38 amino acid sequences of lupin lipases with predicted vacuolar localization was compared ( Table 1 ). As reported previously, the Atg15 yeast possesses lipolytic activity and is involved in autophagic body degradation [ 11 , 12 , 13 , 14 , 23 , 24 , 25 ]. Our analysis revealed that three lupin lipases (XP_019430451.1, XP_019425758.1, and XP_019420123.1) had high amino acid sequence similarity to the Atg15 yeast ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The amino acid sequence of the Atg15 (QHB07198.1_SC) yeast with 38 amino acid sequences of lupin lipases with predicted vacuolar localization was compared ( Table 1 ). As reported previously, the Atg15 yeast possesses lipolytic activity and is involved in autophagic body degradation [ 11 , 12 , 13 , 14 , 23 , 24 , 25 ]. Our analysis revealed that three lupin lipases (XP_019430451.1, XP_019425758.1, and XP_019420123.1) had high amino acid sequence similarity to the Atg15 yeast ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 87%
“…The Atg15 yeast possesses lipolytic activity and is one of the enzymes whose involvement in the degradation of the autophagic body has been confirmed [ 11 , 12 , 13 , 14 , 23 , 24 , 25 ]. Saccharomyces cerevisiae yeast lacking Atg15 accumulated autophagic bodies in vacuoles, demonstrating its essential role in autophagic degradation [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outer membrane of the autophagosome fuses with the vacuole, which results in the release of the inner membrane-bound structure, the autophagic body, into the vacuolar lumen, allowing degradation by the vacuolar lipase Atg15 and a range of proteases. 1 , 2 , 3 , 4 , 5 , 6 Degradation products arising from autophagy, such as amino acids, are subsequently transported back to the cytoplasm for reuse. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%